2022
DOI: 10.3390/ijms23105846
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of MicroRNA Expression and Potential Role in the Regulation of Drug-Resistant Genes in Doxorubicin and Topotecan Resistant Ovarian Cancer Cell Lines

Abstract: Epithelial ovarian cancer has the highest mortality among all gynecological malignancies. The main reasons for high mortality are late diagnosis and development of resistance to chemotherapy. Resistance to chemotherapeutic drugs can result from altered expression of drug-resistance genes regulated by miRNA. The main goal of our study was to detect differences in miRNA expression levels in two doxorubicin (DOX)- and two topotecan (TOP)-resistant variants of the A2780 drug-sensitive ovarian cancer cell line by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…The aberrant over-expression and activation of FOXM1 is the key molecular alteration in ovarian cancers and is associated with poor prognosis and chemotherapy resistance [2]. Doxorubicin is one of the most commonly used anticancer drugs approved by the FDA for ovarian cancer, and it is one of the most important drugs used as a second line of chemotherapy for platinum-resistant patients [49].…”
Section: Stl001-induced Foxm1 Suppression Sensitizes Human Cancers Of...mentioning
confidence: 99%
“…The aberrant over-expression and activation of FOXM1 is the key molecular alteration in ovarian cancers and is associated with poor prognosis and chemotherapy resistance [2]. Doxorubicin is one of the most commonly used anticancer drugs approved by the FDA for ovarian cancer, and it is one of the most important drugs used as a second line of chemotherapy for platinum-resistant patients [49].…”
Section: Stl001-induced Foxm1 Suppression Sensitizes Human Cancers Of...mentioning
confidence: 99%
“…In the literature, increased expression of miR-99a-5p was reported in nonmuscle invasive bladder cancer (Kaba et al 2023), cisplatin-resistant esophageal cancer cells (Pandey et al 2023), topotecan resistant ovarian cancer cell lines (Stasiak et al 2022), cisplatin resistant ovarian cancer cell lines (Kazmierczak et al 2022), diffuse large B-cell lymphoma with chemotherapy resistance (Feng et al 2019), and signet-ring cell carcinoma, a histological subtype of gastric cancer (Saito et al 2020). In parallel with these studies, it has been shown that exosomal miR-99a-5p is elevated in the serum of ovarian cancer patients and promotes cancer cell invasion by increasing fibronectin and vitronectin expression in adjacent peritoneal mesothelial cells (Yoshimura et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…miR-508-3p [ 29 ] and miR-134 [ 30 ], which are sponged by CircETDB1 and LINC01118, respectively, can posttranscriptionally regulate the expression of ABCC1. ABCG2 is involved in topotecan resistance in ovarian cancer, which is associated with miR-212-3p downregulation [ 31 ].…”
Section: Mechanisms Of Drug Resistance In Ovarian Cancermentioning
confidence: 99%